2018
DOI: 10.4317/medoral.22428
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of oral and maxillofacial pathology in a pediatric population from Rio de Janeiro–Brazil over a 75-year period

Abstract: BackgroundThe aim of this study was to analyze the distribution of oral and maxillofacial lesions affecting children and adolescents patients from a single oral pathology laboratory from Rio de Janeiro, Brazil.Material and MethodsOral and maxillofacial lesions biopsied in patients younger than 19-years were retrieved from the oral pathology files of the Department of Oral Diagnosis and Pathology, School of Dentistry, Federal University of Rio de Janeiro over a 75-year period (1942-2017). The clinical data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
5
12
1
3
Order By: Relevance
“…In benign tumour/tumour‐like lesions, non‐odontogenic was the most common (97.3%) and this was similar with other studies that included children from a wider age range 11,12,15 . Haemangioma appeared to be the most common lesion in the non‐odontogenic category, which was in accordance with children aged 0‐5 years as reported by Wang et al 13 and other wider age range studies 4,7,11 . It, however, was second after fibroma among 0‐5 years as reported by Lei et al 12 The second most common lesion under tumour/tumour‐like category was malignant non‐odontogenic (27.0%) and benign odontogenic (1.6%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In benign tumour/tumour‐like lesions, non‐odontogenic was the most common (97.3%) and this was similar with other studies that included children from a wider age range 11,12,15 . Haemangioma appeared to be the most common lesion in the non‐odontogenic category, which was in accordance with children aged 0‐5 years as reported by Wang et al 13 and other wider age range studies 4,7,11 . It, however, was second after fibroma among 0‐5 years as reported by Lei et al 12 The second most common lesion under tumour/tumour‐like category was malignant non‐odontogenic (27.0%) and benign odontogenic (1.6%).…”
Section: Discussionsupporting
confidence: 88%
“…Despite differences between studies in terms of patients’ age range, classification of oral maxillofacial lesions, and study periods, all studies reported mucous extravasation cysts as the most frequent lesion and ranged from 17.4% to 24.5% 4,6,12,13 which was less than the 51.1% in our study. Additionally, although there were variations in the top 10 most common lesions in a few studies, mucous extravasation cysts remain more common than pyogenic granulomas, which, in turn, were more frequent than dental follicles 3,10‐12 .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Odontogenic cysts are among the commonest lesions encountered in children. [5,6] According to Manor et al [7] among the cystic lesions seen in children, developmental cysts were found at higher rate. A prevalence study by Li et al [3] on the occurrence of developmental cysts in children showed that 97.8% of the encountered lesions were dentigerous cyst and Keratocystic Odontogenic Tumour (KCOT).…”
Section: Discussionmentioning
confidence: 97%
“…A incidência da mucocele oral entre os sexos permanecem inconclusivas 7,8 . Zanotto et al 9 em um levantamento das lesões provenientes das glândulas salivares menores diagnosticadas descreve uma predileção pelo gênero masculino (50,84%), sem no entanto significância estatística.…”
Section: Discussionunclassified